Alterations of grey matter volumes and network-level functions in patients with stable chronic obstructive pulmonary disease. (16th February 2020) - Wang, Wei; Wang, Peng; Li, Qingchu; Peng, Zhaohui; Wang, Xiang; Wang, Gang; Hou, Jingming; Fan, Li; Liu, Shiyuan
Highlights: COPD patients show reduced grey matter volume in the supramarginal gyrus, posterior midcingulate cortex and right middle occipital gyrus. COPD patients show decreased functional connectivity within the visual network, frontoparietal network and other brain regions. Decreased connectivity within visual and frontoparietal network were correlated with the Cognitive function and disease duration in COPD. Abstract: Objective: The purpose of this study was to investigate structural and functional alterations of the brain in the patients with stable chronic obstructive pulmonary disorder (COPD) and further investigate how these alterations correlated to parameters of pulmonary function test, cognitive function and disease duration in patients with COPD. Method: Forty-five patients with stable COPD and forty age- and gender-matched healthy controls were enrolled into this study. Both resting-state fMRI and structural MRI were acquired for each participant. Voxel-based morphology was utilized to analyze alterations of the grey matter volume (GMV), and the seed-based resting-state functional connectivity (FC) was used to evaluate the network-level functional alterations. Results: Compared to healthy controls, patients with stable COPD showed decreased GMV in the left supramarginal gyrus/precentral gyrus (SMG/PreCG), bilateral posterior midcingulate cortex (pMCC), right middle occipital gyrus (MOG) and right SMG. Furthermore, COPD patients mainly showed decreased FC within the visual network, frontoparietal network and other brain regions. Subsequent correlational analyses revealed that the decreased FC within visual network, frontoparietal network were positively correlated with the Montreal Cognitive Assessment score, language-domain score, attention-domain score and disease duration in patients with COPD. Conclusion: Our findings provided evidence that COPD patients showed decreased GMV and regional and network-level functional alterations within the visual network, frontoparietal network and other networks. We speculated that atrophic GMV and FC of visual network and frontoparietal network are involved in the neural mechanism of mild cognitive impairment in stable COPD patients.